THE RELATIONSHIP BETWEEN THREE CONSTRUCTS OF EMPLOYEE ATTITUDES TOWARDS ORGANIZATIONAL CHANGE - Mega Asri Zona; Rini Sarianti; Chichi Andriani (Jurnal Ilmiah Manajemen & Bisnis, 2020)
The Relationship between Three Constructs of Employee Attitudes towards Organizational Change. This research examines three constructs that represent employee attitudes towards organizational change; commitment to change, readiness for change, and openness to change. This research analyzed the influence of readiness for change and openness to change on employee commitment to change in public sector organization in West Sumatra. It would help the public organization to understand their employee attitudes during change. This research is a quantitative research. Respondents are 100 employees in public sector organization in West Sumatra Province. Data was collected using questionnaire. The result shows both independent variables; openness to change and readiness to change have positive and significant effect on commitment to change. Employee commitment to changes in this research is influenced by the readiness for change and openness to change. These results show that employees in public organization in West Sumatra Province felt that if they would benefit from change, then they would do what was needed to make the change successful. Keywords: employee attitudes towards change, commitment to change, readiness for change, openness to change